Growth hormone and Insulin like growth factor -1 in relation to prostate cancer and benign prostatic hyperplasia - Waheed, Intissar N.; Ra’uf Salh, Shilan M. (Science Journal of University of Zakho, 2016)
The present study investigate the role of growth hormone (GH) in the pathophysiology of prostate and the role of insulin like growth factor I (IGF-I) as a risk factor in aged male patients with prostate cancer (PCa) and benign prostatic hyperplasia (BPH). For this purpose, 40 patients with PCa and BPH (54-85 yr.), and 10 control subjects (47-75 yr.) confirmed by digital rectal examination (DRE) and prostate specific antigen (PSA) levels, were enrolled in this study. Blood samples and biopsies were collected from cases while for the control, only blood sera were used. Gleason grading system was used to determine histological pattern of Hematoxylin and Eosin stained sections. Sera GH and IGF-I were measured for all the samples using (ELISA) technique. Biopsy results revealed that 10 cases were identified as PCa with different Gleason grades (3, 4, and 5) depending on five histological patterns, and 30 cases were identified as BPH. Compared with control values, GH level was significantly higher (P< 0.05) in PCa and BPH patients, with no significant differences between PCa and BPH groups (P> 0.05) concerning serum GH level. Statistical analysis also indicates that serum levels of IGF-I was higher and significantly (P< 0.05) associated with PCa compared with controls. Serum IGF-I also showed significant difference between control and BPH patients, and between BPH and PCa patients. The present study demonstrated that the association between serum IGF-I levels and PCa was highly significant in age 60 and declined with the age (p= 0.047), but in concern to the histological grade, IGF-I showed no significant differences (p=0.894) with the progression of disease. In conclusion it's appeared that, IGF-I play an important role in the etiology of PCa and BPH.
Keywords: Prostate cancer; Benign prostatic hyperplasia; Growth hormone; Insulin like growth factor I